Determining the effectiveness of including spatial information into a nematode/nutsedge pest complex model - Vetter, Joel (Kansas State University, 2012)
An experiment was performed in 2005-2006 to determine if the variety of an alfalfa (Medicago sativa) crop rotation can effectively reduce the pest complex consisting of the yellow and purple nutsedge (YNS & PNS) weeds and the southern root-knot nematode (SRKN). During the 2005-2006 growing season, six months were selected to take samples from the alfalfa field (three months in 2005 and three months in 2006). The field was divided into 1m x 2m quadrats. Each month eighty quadrats were randomly selected. The counts of PNS, YNS and a soil sample (analyzed for the count of juvenile SRKN) were taken from each quadrat. In this study, two different ways were examined use [i.e. using] spatial information provided from the experiment to alter the original model. First spatial information was treated as fixed effects. Second spatial information was treated as random effects by modifying the residual variance matrix using various “spatial” variance-covariance structures. The results were compared to the original Poisson model and the spatial models to each other but did not have an effective way of comparing random effects models with the fixed effects models. For this data, the use of spatial statistics did not improve the original model consistently. This may be partly because of the nature of the experiment. The alfalfa effectively reduced the YNS, PNS, and SRKN counts. The spatial information was generally more useful earlier in the experiment when the YNS, PNS, and SRKN populations were denser.
Keywords: Nematode; Nutsedge; Spatial; Statistics (0463)